Brotherhood & Cooperation : Crossbow / Muhammad Zulkhairee Md Zabani...[et al.] - Md Zabani, Muhammad Zulkhairee; Norazman, Norshafiq Rizal; Hisyam, Wajihuddin; Mohd Hamzah, Muhammad Rezuan; Mohd Noor, Muhammad Faiz (2014)
Our company Brotherhood & Cooperation provide a toys which is a crossbow for kids in a range of 7-12 years old. Our product has a simple design, suitable and easy for kids to play. The price is affordable and cheaper if compare to other company which sells quite similar product. Besides that, our targeted customer is not only for a kids around ages that stated above, but also can be played by teenagers. Since our business is still new, so our primary market target area is focus on Johor Bahru. We hope, we can expand our company's empire by producing another safe product and be the most popular toys company in the world.